2004
DOI: 10.1016/j.eplepsyres.2004.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of three NMDA receptor antagonists in the treatment of prolonged status epilepticus

Abstract: Three different classes of NMDA receptor antagonists were compared for their effectiveness in terminating prolonged status epilepticus (SE), induced by continuous hippocampal stimulation. Animals were treated after 150 min of SE by intraperitoneal administration of increasing doses of 3-((R,S)-2-carboxypiperazin-4-yl)-propyl-1-phosphonic acid (CPP), MK-801 (dizocilpine), ifenprodil, or saline. EEG recordings were used to determine seizure termination. The first experiment (n = 57 animals) determined the most e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 45 publications
2
29
1
Order By: Relevance
“…Limited data are available on the use of this infusion therapy in humans, although its use in RSE has theoretic advantages, there is evidence that excessive NMDA excitatory receptor-mediated transmission is an important mechanism of persistent neuronal firing in the setting of downregulation of gaminobutyric acid receptors. The evidence for efficacy of ketamine is largely anecdotal [60]. The reported adverse effects relate to its use as an analgesic, where hallucinations and other transient psychotic sequelae are reported.…”
Section: Ketaminementioning
confidence: 95%
“…Limited data are available on the use of this infusion therapy in humans, although its use in RSE has theoretic advantages, there is evidence that excessive NMDA excitatory receptor-mediated transmission is an important mechanism of persistent neuronal firing in the setting of downregulation of gaminobutyric acid receptors. The evidence for efficacy of ketamine is largely anecdotal [60]. The reported adverse effects relate to its use as an analgesic, where hallucinations and other transient psychotic sequelae are reported.…”
Section: Ketaminementioning
confidence: 95%
“…In addition, ifenprodil blocks the Nand P-type voltage-dependent Ca 2+ channels [32] . The anticonvulsive activity of ifenprodil has been shown in several experimental models of epilepsy like amygdale-kindled rats [19] and prolonged status epilepticus [17] . Wang and Bausch [16] observed that the electrical discharges induced by bicuculin (GABA antagonist) in a hippocampal in vitro culture could be inhibited by ifenprodil.…”
Section: Discussionmentioning
confidence: 99%
“…in a volume of 0.5 ml/kg rat body weight. The ifenprodil doses and the time of administration were chosen according to previous researches [17,18] . Lindane, DMSO and ifenprodil are produced by Sigma-Aldrich Chemical Co., USA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ketamine is used in the same fashion as other coma-inducing agents; that is, IV bolus, followed by maintenance infusion. The evidence for efficacy of ketamine is largely anecdotal [47,81].…”
Section: Multiple Continuous Infusion Therapymentioning
confidence: 99%